Deriving An Object Dislocation Asymmetry In Luganda - Ranero, Rodrigo (My University, 2019)
In this paper, I document and analyze an object-dislocation asymmetry in Luganda (Bantu: JE15) that becomes apparent only upon comparing double object left-dislocation versus double object right-dislocation. If two objects are left-dislocated, the object markers (OMs) on the verb are strictly ordered OMTHEME > OMGOAL/BEN and the dislocated objects are ordered freely, either goal/ben > theme or theme > goal/ben. In contrast, if two objects are right-dislocated, the objects cannot be freely ordered — two right-dislocated objects must be ordered goal/ben > theme. However, in double object right-dislocation, the OMs must also be ordered OMTHEME > OMGOAL/BEN . I propose that this asymmetry can be captured if left-dislocated objects are base generated in their surface position, whereas right-dislocated objects are derived via movement. Several predictions concerning binding and superiority effects are borne out, providing support for the analysis.
Keywords: Luganda; object right-dislocation; object dislocation asymmetry; Bantu